Of the traditional determinants of migration until the impulsioneds by liquid modernity in perspectives of Alice's Adventures in Wonderland and of Dry Lives - Pereira Neto, Claudeci (Geosaberes, 2019)
The aim of this article is to describe the coexistence of the traditional motivators of the migratory act with the new determinants boosted by BAUMAN's “liquid modernity” (2001), through the analysis of Alice's dialogues with the Cheshire Cat and with the Queen of Hearts present in Alice's Adventures in Wonderland , by Lewis CARROLL. Also through the examination of the life and actions of the family of the retreatants of the group of “sertanejos” in the book Dry Lives , by Graciliano RAMOS. We realize that new factors resulting from rapid social, economic and technological transformations irreversibly affect the way where the production is organized and the relationship between capital and work. However, the fluid phase of capitalism overlapped, but not eliminated, the heavy phase of capitalism, which is likely to influence the flow of migrants, especially between large cities in developed and developing countries.